2010
DOI: 10.1007/s10695-009-9348-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in aerobic capacities and reactive oxygen species metabolism in the silver eel

Abstract: Silver European eels (Anguilla anguilla L.) need to develop important aerobic capacities to cope with their long fasting spawning migration at depth, particularly males which are about half the size of females. Moreover, they have to face potential oxidative stress because reactive oxygen species (ROS) production is linked to the increase in metabolic rate. Thus, aerobic metabolism was globally evaluated in male and female silver eels exposed to a 10.1 MPa hydrostatic pressure (1,000 m depth). Oxygen consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
1
7
0
1
Order By: Relevance
“…In the present study, GPX and CAT exhibited opposite correlation patterns with size, which is similar to observations in brain tissue of A. antennatus, (Mourente and Díaz-Salvago, 1999). Furthermore, GPX and GR activities exhibited a significant overall negative relationship with size, which is consistent with the general idea of metabolic scaling of antioxidant activities as a result of decreasing oxygen consumption (and associated ROS production) with increasing size (Amérand et al, 2010).…”
Section: A Antennatussupporting
confidence: 87%
“…In the present study, GPX and CAT exhibited opposite correlation patterns with size, which is similar to observations in brain tissue of A. antennatus, (Mourente and Díaz-Salvago, 1999). Furthermore, GPX and GR activities exhibited a significant overall negative relationship with size, which is consistent with the general idea of metabolic scaling of antioxidant activities as a result of decreasing oxygen consumption (and associated ROS production) with increasing size (Amérand et al, 2010).…”
Section: A Antennatussupporting
confidence: 87%
“…Essa depleção da atividade da CAT pode ter ocorrido devido à saturação enzimática com o aumento da exposição aos BTEX e, consequentemente, de seus metabólitos. Entretanto, estudos em humanos comparando a atividade enzimática da CAT de populações expostas e entre homens e mulheres, além de escassos, possuem resultados controversos e não conclusivos, necessitando-se ainda de mais estudos nessa área [36][37][38] .…”
Section: Discussionunclassified
“…Oxidative stress is quickly becoming recognized as a physiological consequence of both natural (i.e., migration; Costantini et al 2008;Amérand et al 2010;parental care;Wilson et al 2012) and anthropogenic (i.e., bycatch; Romero et al 2007) activities. In semelparous pink salmon, the final reproductive migration is an enormously challenging phase with numerous selective pressures including osmoregulatory challenges, increased temperatures, and increased pathogen burden ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, pigeons {Columba livia) that flew for more than 3 h had increased concentrations of reactive oxygen metabolites and decreased antioxidants, resulting in an overall increase in oxidative stress compared with pigeons that flew for shorter flights . Studies of the reproductive migration of European eels {An-guilla anguilla L.) found that despite a 6,000-km-long fasting migration through the Atlantic Ocean, these semelparous eels experienced minimal oxidative stress (Amérand et al 2010). Oxidative stress remains a largely unexplored physiological trade-off of long-distance migration.…”
Section: Introductionmentioning
confidence: 99%